Students’ perceptions of vocabulary recall and engagement in Wordwall-based gamified learning - Elma Ziyadatil Ulya; Nadiah Ma'mun; Nuna Mustikawati Dewi (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
This study explores students’ perceptions of Wordwall-based gamified learning during four consecutive recount-text vocabulary lessons in a junior high school EFL classroom. The research was motivated by the need to make vocabulary learning more engaging while supporting students perceived ability to recall targeted words. Using a quantitative descriptive design, data were collected from twenty-nine ninth-grade students through a 25-item self-developed questionnaire grounded in theoretical dimensions of behavioral, emotional, and cognitive engagement. No vocabulary pre- or post-test was used; therefore, all findings reflect students’ self-reported experiences rather than objective retention. The results showed consistently high mean scores across the three engagement dimensions and indicated that students perceived Wordwall as enjoyable, motivating, and supportive of their vocabulary recall. Repetition, instant feedback, and interactive game features made vocabulary practice more meaningful from the learners’ perspective. This study contributes classroom-based evidence on multidimensional engagement in Wordwall-integrated EFL lessons and highlights the potential of gamified learning tools to create active and student-centered vocabulary instruction when used purposefully.